Estimating the value of mangrove leaf litter in sesarmid crab diets: the importance of fractionation factors - Mackenzie, R.A.; Cormier, N.; Demopoulos, A.W. (Bulletin of Marine Science, 2020)
Sesarmid crabs play an important role in organic matter and carbon cycling of mangrove forests. Visual observations and gut content studies have verified that sesarmid crabs are feeding on mangrove leaves, yet stable isotopes of carbon and nitrogen (13C and 15N) have indicated that leaf litter is not assimilated as a food source. Sesarmid crabs tend to be much more enriched in 13C than leaf litter (0.9‰ – 11.6‰) and have C values that are often more like microphytobenthos (MPB). General 13C trophic enrichment factors (TEF; 0.1‰ – 0.5‰) suggest crabs feed more heavily on MPB. Field and laboratory-based evidence reveal that general 13C TEF for crabs feeding on mangrove leaves may be incorrect and much greater than 0.1‰ – 0.5‰. A food web study conducted annually over 2 yrs revealed a shift in the δ13C and δ15N of Parasesarma sp. crabs similar to mangrove leaves also sampled. This suggested Parasesarma sp. may be feeding more heavily on mangrove leaves than previously reported despite crabs being 4.4‰ – 11.6‰ more enriched in 13C than mangrove leaves. A laboratory feeding study confirmed that average 13C TEF between Parasesarma sp. and decayed Rhizophora sp. leaves was 3.3‰ (SE 0.5). The Stable Isotope Analysis in R package (SIAR) used with our TEF and the general 0.5‰ 13C TEF revealed that published TEFs may underestimate mangrove leaf contributions to sesarmid crab diets on average by 33.3% (SE 0.1) and overestimate MPB and epiphytic algal contributions by 31.3% (SE 0.1). Food web studies in mangroves and other ecosystems will continue to inaccurately identify important food resources or food web structures unless more accurate and species-specific isotope fractionation values are determined.